2010
DOI: 10.3892/or_00000914
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted imaging in evaluating therapeutic efficacy after transcatheter arterial chemoembolization for hepatocellular carcinoma

Abstract: Abstract. The decision to repeat transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) is based on correct evaluation of response to therapy. The purpose of this study was to investigate whether apparent diffusion coefficient (ADC), a quantitative parameter of diffusionweighted imaging (DWI), can predict early HCC recurrence after TACE. Results obtained using this method were compared with those using iodized-oil computed tomography (CT). DWI was performed on 25 patients with 36 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…Therefore, many recent studies have examined its clinical applications, especially for oncologic imaging. In terms of HCC, DWI can improve lesion detection [79][80][81], predict the histological grade of HCC [82][83][84][85], and assess treatment response and recurrence [86][87][88][89][90].…”
Section: Dual Energy Ctmentioning
confidence: 99%
“…Therefore, many recent studies have examined its clinical applications, especially for oncologic imaging. In terms of HCC, DWI can improve lesion detection [79][80][81], predict the histological grade of HCC [82][83][84][85], and assess treatment response and recurrence [86][87][88][89][90].…”
Section: Dual Energy Ctmentioning
confidence: 99%
“…Mannelli et al [102] reported that ADC quantification could predict response to TACE: HCCs with poor/incomplete response (< 50% necrosis) had significantly lower pre-and post-TACE ADC values than lesions with good/complete response. Kubota et al [103] reported that the percent ADC value modification after therapy was significantly higher in non-relapsed HCCs (85.2% ± 12.4%) as compared to lesions with disease relapse (8.0% ± 56.7%, P < 0.001). Konstantinidis et al [104] reported that DCE-MRI could predict treatment outcome after hepatic arterial infusion (HAI) of floxuridine and dexamethasone (with or without bevacizumab) in advanced intra-hepatic Kamel et al [86] 38 0, 500 1.51 1.70 HCC TACE Sahin et al [87] 74 0, 50, 400, 800 1.10 1.27 HCC TACE Kamel et al [88] 24 0, 50, 750 1.86 2.13 HCC TACE Chen et al [89] 20 0, 500 1.56 2.09 HCC TACE Yuan et al [90] 41 0, 500 2.22 1.42 HCC TACE Deng et al [98] 6 0, 500 1.30 2.23 HCC TARE Kamel et al [99] 13 0, 500 1.65 1.95 HCC TARE Rhee et al [100] 20 0, 500 1.64 1.82 HCC TARE Mannelli et al [102] 36 0, 50, 500 1.64 1.92 HCC TACE Kubota et al [103] 25 0, 500 CCCs: AUC90 and AUC180 were significantly higher in ≥ 3-year survivors than < 3-year survivors.…”
Section: Primary Liver Tumorsmentioning
confidence: 99%
“…Enhanced areas in the embolization site on gadolinium-enhanced MRI presumably represent viable tumor (table 3) [53,54,55,56,57] but could also result from post-treatment granulation tissue [58]. In addition, diffusion-weighted MRI is a new kind of functional imaging technology that can explore the random diffusion motion of water molecules in vivo.…”
Section: Principle Of Tumor Response Assessment To Tace For Hccmentioning
confidence: 99%
“…However, diffusion-weighted MRI is known to have limitations such as a relatively poor signal-to-noise ratio and high sensitivity to pulsatile or susceptibility artifacts, degrading the ability to detect lesions. A new quantitative measurement on diffusion-weighted MRI may allow effective evaluation of the efficacy of TACE for HCC and correctly reveal recurrent tumors [56,57]. …”
Section: Principle Of Tumor Response Assessment To Tace For Hccmentioning
confidence: 99%